2003
DOI: 10.4049/jimmunol.171.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Rho Kinase Promotes Alloimmune Responses by Regulating the Proliferation and Structure of T Cells

Abstract: Coordinated rearrangements of the actin-myosin cytoskeleton facilitate early and late events in T cell activation and signal transduction. As many important features of cell shape rearrangement involve small GTP-binding proteins, we examined the contribution of Rho kinase to the functions of mature T cells. Inhibitors of the Rho kinase pathway all had similar actions to inhibit the proliferation of primary lymphocyte cultures. Likewise, transfection of the human Jurkat T cell line with a dominant negative, kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 52 publications
3
59
0
Order By: Relevance
“…Rac, Ras, Cdc42, Rap, and RhoA activation assays Levels of Rac1-, Rac2-, Cdc42-, RhoA-, Rap-, and Ras-bound GTP were determined by established immunoblot techniques (Upstate Biotechnology) (15,25). In brief, T cells were stimulated for indicated periods of time in the presence or absence of azathioprine, 6-MP, or 6-TG.…”
Section: Analysis Of 6-thio-gtp Binding To Gtpasesmentioning
confidence: 99%
“…Rac, Ras, Cdc42, Rap, and RhoA activation assays Levels of Rac1-, Rac2-, Cdc42-, RhoA-, Rap-, and Ras-bound GTP were determined by established immunoblot techniques (Upstate Biotechnology) (15,25). In brief, T cells were stimulated for indicated periods of time in the presence or absence of azathioprine, 6-MP, or 6-TG.…”
Section: Analysis Of 6-thio-gtp Binding To Gtpasesmentioning
confidence: 99%
“…The Rho GTPase family members have been shown to play a pivotal role in regulating changes in actin cytoskeleton, which in turn affects many aspects of cellular function (12,24,25). Previous studies have shown that specific inactivation of RhoA kinase activity in T cells resulted in defective TCR/CD3 complex polarization (21,22). Similarly, anergic T cells stimulated with anti-CD3-coated beads displayed impaired actin cup formation at the T cell/ bead interface, due to defects in actin cytoskeleton reorganization (26).…”
Section: Discussionmentioning
confidence: 99%
“…with the specific Rho kinase pharmacological inhibitor Y-27632, resulted in inhibition of IL-2 production in T cells (21,22).…”
Section: Rho Is Involved In Il-2 Expression and This Activity Is Abrmentioning
confidence: 99%
“…These data are consistent with the importance of immunological factors in chronic graft injury. The Rho/ROCK pathway is potentially crucial in mediating immunological as well as nonimmunological injury in chronic graft loss as it is involved in adhesion, migration, proliferation, and cytokine release (Amano et al 1997;Chihara et al 1997;Tharaux et al 2003). The activation of T-cells is involved in alloimmune responses.…”
Section: Rock Inhibition In Chronic Allograft Nephropathymentioning
confidence: 99%
“…The activation of T-cells is involved in alloimmune responses. Here the Rho/ROCK pathway plays a pivotal role in T-cell activation during cellular immune responses by promoting structural rearrangements that are critical for T-cell signaling (Tharaux et al 2003). Besides, a role for Rho/ROCK in HLA class I signaling pathways that have been implicated in the process of chronic rejection has been shown.…”
Section: Rock Inhibition In Chronic Allograft Nephropathymentioning
confidence: 99%